Improving Reading Comprehension through SQ3R Strategy towards Junior High School Students in Tarakan - Asih Riyanti; Nurul Hanna Fauziyyah (International Journal of Community Engagement Payungi, 2025)
Reading comprehension is the ability to read a text, process it, and understand its meaning. It is essential to comprehend a text because if someone is unable to understand it well, this can hinder their achievement of success in education. In schools, students’ reading ability, especially reading comprehension, can be improved through various reading learning methods. This study aims to enhance students’ reading comprehension in SMP 9 Tarakan by utilizing the SQ3R strategy. This study employed a Class Action Research (CAR) approach to address the problems in the study, aiming to improve students’ reading comprehension skills by implementing the Survey, Question, Read, Recite, Review (SQ3R) learning strategy. There has been an increase in reading comprehension skills among grade VII students at SMP 9 Tarakan following the implementation of the SQ3R strategy, which involves surveying, questioning, reading, reciting, and reviewing (SQ3R) in the lesson. This can be seen from the final scores of the evaluation test results carried out by students in Cycle I and Cycle II, which increased from 79.09 to 85.04. The indicators of reading comprehension in this study include identifying the main idea, answering questions, drawing conclusions from the text, and retelling the information in their own words. Additionally, there is reportedly an increase in the achievement of indicators from cycle I to cycle II for each indicator. All assessed indicators identifying main ideas, answering questions, drawing conclusions, and retelling content demonstrated notable increases from Cycle I to Cycle II. These gains were supported by improvements in each SQ3R stage, especially after reflecting on and refining the teaching process. This indicates that the SQ3R strategy effectively enhanced students’ ability to understand and process reading materials.